If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(10x + 2) + 79 + 79 = 180 Reorder the terms: X(2 + 10x) + 79 + 79 = 180 (2 * X + 10x * X) + 79 + 79 = 180 (2X + 10xX) + 79 + 79 = 180 Reorder the terms: 79 + 79 + 2X + 10xX = 180 Combine like terms: 79 + 79 = 158 158 + 2X + 10xX = 180 Solving 158 + 2X + 10xX = 180 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-158' to each side of the equation. 158 + 2X + -158 + 10xX = 180 + -158 Reorder the terms: 158 + -158 + 2X + 10xX = 180 + -158 Combine like terms: 158 + -158 = 0 0 + 2X + 10xX = 180 + -158 2X + 10xX = 180 + -158 Combine like terms: 180 + -158 = 22 2X + 10xX = 22 Reorder the terms: -22 + 2X + 10xX = 22 + -22 Combine like terms: 22 + -22 = 0 -22 + 2X + 10xX = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-11 + X + 5xX) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-11 + X + 5xX)' equal to zero and attempt to solve: Simplifying -11 + X + 5xX = 0 Solving -11 + X + 5xX = 0 Move all terms containing X to the left, all other terms to the right. Add '11' to each side of the equation. -11 + X + 11 + 5xX = 0 + 11 Reorder the terms: -11 + 11 + X + 5xX = 0 + 11 Combine like terms: -11 + 11 = 0 0 + X + 5xX = 0 + 11 X + 5xX = 0 + 11 Combine like terms: 0 + 11 = 11 X + 5xX = 11 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 29x-32x=8-11 | | t-4=-29 | | 24/1x-8/10 | | x(5x+23)=2x^2-3x+9 | | 8x-1=6s-5 | | M(7x+5)=180 | | (7y-4)/13 | | -26+22=-6x+8x | | 2(7-2x)=-3(x-5) | | 9/7t=-8/9 | | X(7x+5)+104+50=180 | | 6x-4y-5z-12=0 | | 110+5x-20=180 | | 2.7x+0.8=3x | | 6x-2(-6+3x)=7 | | 3t^4-2t^2-8=0 | | 10w-17w=21 | | -100+30=120+90 | | 3(4s-16)-5s=-5 | | 10^6/4 | | M(6x+2)=180 | | -0.8x=-56 | | 2y=685x+85 | | -7h+-9h= | | 1x-y=7 | | t=7/4=11 | | 0.7x=-105 | | y=5*e^2*x | | 2y=685+85 | | X(6x+2)+27+31=180 | | 10*(9*1)=(n*9)*1 | | -7a+-9h= |